A mRNA Vaccine Encoding for a RBD 60-mer Nanoparticle Elicits Neutralizing Antibodies and Protective Immunity Against the SARS-CoV-2 Delta Variant in Transgenic K18-hACE2 Mice - Brandys, Pascal; Montagutelli, Xavier; Merenkova, Irena; Barut, Güliz T.; Thiel, Volker; Schork, Nicholas J.; Trüeb, Bettina; Conquet, Laurine; Deng, Aihua; Antanasijevic, Aleksandar; Lee, Hyun-Ku; Valière, Martine; et al. (Frontiers in Immunology, 2022)
Two years into the COVID-19 pandemic there is still a need for vaccines to effectively control the spread of novel SARS-CoV-2 variants and associated cases of severe disease. Here we report a messenger RNA vaccine directly encoding for a nanoparticle displaying 60 receptor binding domains (RBDs) of SARS-CoV-2 that acts as a highly effective antigen. A construct encoding the RBD of the Delta variant elicits robust neutralizing antibody response, and also provides protective immunity against the Delta variant in a widely used transgenic mouse model. We ultimately find that the proposed mRNA RBD nanoparticle-based vaccine provides a flexible platform for rapid development and will likely be of great value in combatting current and future SARS-CoV-2 variants of concern.